Airborne bacterial communities and antibiotic resistance gene dynamics in PM2.5 during rainfall. (January 2020) - Ouyang, Wei; Gao, Bing; Cheng, Hongguang; Zhang, Lei; Wang, Yidi; Lin, Chunye; Chen, Jing
Highlights: PM2.5 under different rainfall processes were studied with on-site synchronous samples. Airborne bacterial communities in PM2.5 response to rainfall intensities were analyzed. Abundances of antibiotic resistance genes varied during rainfall process. Meteorological conditions of rain events and physicochemical properties of PM2.5 are the key factors. Abstract: The biotoxicity and public health effects of airborne bacteria and antibiotic resistance genes (ARGs) in fine particulate matter (PM2.5 ) are being increasingly recognized. The characteristics of bacterial community composition and ARGs in PM2.5 under different rainfall conditions were studied based on the on-site synchronous measurements in downtown Beijing. Marked differences were evident in the bacterial community characteristics of PM2.5 before, during, and after rain events (p < 0.05). The rain intensities affected the bacterial community abundance in PM2.5 and heavy rain had greater washing effects. The Proteobacteria (phylum level), α-Proteobacteria (class level), Pseudomonadales (order level), Pseudomonadaceae (family level), and Cyanobacteria (genus level) were the dominant bacterial taxa associated with PM2.5 in Beijing during rain events. However, the bacteria at each level that displayed the biggest percentage variance was not the dominant type under different rain intensities. The ermB, tetW, and mphE genes were the primary ARGs, with abundances of 18 to 30 copies/m 3, which was a relatively smaller value than other observations. Real-time monitoring of the meteorological condition of rain events and physicochemical properties of PM2.5 were used to identify the main factors during rainfall. The bacterial community was sensitive to the ionic and metal element components of PM2.5 during rainfall. The abundance of ARGs was closely correlated with some groups of the bacterial community, which were also close to the initial value before the rain. Statistical analysis demonstrated that temperature, relative humidity, and duration of rain were the primary meteorological factors for the biological characteristics. The ionic species, rather than metal elements, in PM2.5 were the sensitive factors for the bacteria community and ARGs, which varied at the phylum, class, order, family, and genus levels. The observations provide insights for the biological risk assessment in an urban rainfall water and the potential health impact on citizens.